Ubiquity : the science of history-- or why the world is simpler than we think - Buchanan, Mark. (New York : Crown Publishers, 2001)
Tells the story of the scientific discovery that there is a natural structure of instability woven into the fabric of the world that leads to catastrophes of all kinds--such as earthquakes, forest fires, and stock market crashes--and makes them impossible to predict.
First published: Great Britain : Weidenfeld & Nicolson, 2000.
Includes bibliographical references (p. 245-259) and index.
Booklist.
Library Journal.
Publisher's Weekly.
Adult
Keywords: Causality (Physics); Pattern formation (Physical sciences); Causality (Physics); Chaos (Science); History -- Philosophy; Science -- Philosophy